2017
DOI: 10.1111/codi.13821
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative complications in individuals aged 70 and over undergoing elective surgery for colorectal cancer

Abstract: This study shows that in-hospital medical and surgical complications after surgery for colorectal cancer in patients ≥ 70 years old are frequent and that complications lead to less favourable outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 59 publications
8
21
0
1
Order By: Relevance
“…[21][22][23][24] In fact, our results also confirm prior findings on the increased LOS in >60-years-old after donor nephrectomy. [21][22][23][24] In fact, our results also confirm prior findings on the increased LOS in >60-years-old after donor nephrectomy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…[21][22][23][24] In fact, our results also confirm prior findings on the increased LOS in >60-years-old after donor nephrectomy. [21][22][23][24] In fact, our results also confirm prior findings on the increased LOS in >60-years-old after donor nephrectomy.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, our findings that >60-years-old exhibited a higher incidence of postoperative ileus after surgery and had longer LOS are not novel, as multiple groups have observed this in large cohorts of geriatric patients undergoing emergent and elective surgery. [21][22][23][24] In fact, our results also confirm prior findings on the increased LOS in >60-years-old after donor nephrectomy. 14 Thus, our findings demonstrate that perioperative morbidity and short-term outcomes are a minimal acceptable concession for the benefits of a living donor kidney to the respective recipient.…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, the number of surgical complications after laparoscopic treatment was 10.7%. Similar results are presented a Belgian prospective study evaluating treatment outcomes in 2009-2015 in patients who reported 17.9% complications [8], and by British researchers -12.4% [9]. In the group of older patients (>65-years-old) the number of complications was greater, which is confirmed by Cummings et al, who reported the proportion of complications at 21.5% and early mortality at 3.3% [10].…”
Section: Discussionsupporting
confidence: 81%
“…In the group of patients who underwent surgery in Kielce, surgical site infection after laparoscopy was reported in seven patients, representing 0.5% of the group. The results presented by other authors range from 0% (Cummings et al [10]) to 12.1% (Fagard et al [8]).…”
Section: Discussionmentioning
confidence: 84%
“…As a summary, the overall complication rate was 42.02 %, while mortality represented 7.97 %and was statistically significant in favor of patients who presented post-operative complications. Aspects stated before can be found in multiple studies (28)(29)(30)(31)(32)(33).…”
Section: Resultsmentioning
confidence: 94%